2019
DOI: 10.5815/ijieeb.2019.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Keeping with the Global Trends: An Evaluation of Accessibility and Usability of Nigerian Banks Websites

Abstract: The growing need for accessible websites cannot be overemphasized as it has posed a major challenge in the world of Information and Communication Technology (ICT). Most businesses have gone online in order to improve their market value; the banking sector is not an exception. In an attempt to satisfying customers, websites developers have violated most of the websites standards. The banking sector is one area that carries out most of its activities online. Therefore, it is important that their websites be acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The study finds that vulnerabilities are exists in most of the e-commerce sites which causing unsecure for customers to trust their private data. The research [19] demonstrated the website's usability and accessibility issues for Nigerian banks websites. The study applied both manual and automated approach to evaluate the accessibility and usability issues and check the websites standard as defined by Web Accessibility Initiate.…”
Section: Related Workmentioning
confidence: 87%
“…The study finds that vulnerabilities are exists in most of the e-commerce sites which causing unsecure for customers to trust their private data. The research [19] demonstrated the website's usability and accessibility issues for Nigerian banks websites. The study applied both manual and automated approach to evaluate the accessibility and usability issues and check the websites standard as defined by Web Accessibility Initiate.…”
Section: Related Workmentioning
confidence: 87%
“…However, online banking services have previously been reviewed and can be considered as falling under the umbrella of FinTech services. In a study examining the accessibility and usability of ten Nigerian banks [ 23 ], tool-based analyses revealed all the tested websites to harbor accessibility issues, of which failure to provide alternative text was the most frequent. Another common issue was slow user experience due to insufficient performance optimization.…”
Section: Related Workmentioning
confidence: 99%
“…Various studies have investigated website usability using few evaluation tools (Domínguez Vila, Alén González & Darcy 2018;Katuu 2018;Oyefolahan et al 2019). Katuu (2018) evaluated the Mandela Portal website using Google Analytics and was able to identify visitors' geographic origins to formulate strategies on content improvements.…”
Section: Factors That Influence Website Visitsmentioning
confidence: 99%